Evaluation of the communication strategy for promoting physical activity in a cross-company network in Germany: A mixed-methods analysis - Carina Hoffmann; Carina Hoffmann; Andrea Schaller (Frontiers Media S.A., 2022)
IntroductionThe workplace is considered a promising setting for reaching physically inactive adults, but participation quotes in workplace health promotion (WHP) remain low. Regarding the low participation in WHP, the question emerges concerning the importance of health communication strategies. This paper presents the results from the evaluation of the communication strategy of a cross-company network for promoting physical activity and derives findings for the successful communication of measures.Materials and methodsQuantitative and qualitative data sources were used to evaluate the communication strategy. The methods applied included individual semi-structured interviews (n = 14) and the monitoring of the usage of digital communication channels.ResultsThe analysis revealed that the usage of the digital communication channels within this study was subjected to major fluctuations and a variety of factors must be considered when communicating physical activity measures in a cross-company network. It is important to engage in appropriate communication management that explicitly takes the interpersonal communication and the organizational circumstances into account.ConclusionThis study revealed which factors may have an influence on the successful communication of physical activity measures in the context of WHP in cross-company networks. Thus, it makes an important contribution to the transfer of science and practice as it captured relevant questions from the field of WHP.Trial registrationGerman Clinical Trials Register (DRKS)-ID: DRKS00020956; Date of registration: 18 June 2020, https://drks.de/search/de/trial/DRKS00020956.